THE EFFECT OF PRICE, PRODUCT QUALITY AND HEDONISM LIFESTYLE ON DIAMOND SHOPS PURCHASING DECISIONS MEDIATED BY PERCEIVED VALUE AT DIAMOND SHOPS IN MEDAN CITY - Satria Tirtayasa; Febry Ramadhani (SEAN Institute, 2023)
The purpose of this study was to determine and analyze the effect of Price, Product Quality and Hedonism Lifestyle on Diamond Shops Purchasing Decisions mediated by Perceived Value at a Diamond Shops in Medan City (Pasar Central). The method used in this research is to use a quantitative approach method. The unknown population then uses the lemeshow formula with a sample size of 100 respondents. Data obtained by online questionnaire via google form. Data collection techniques used in this study using questionnaires/questions and interviews/interviews. Data analysis techniques in this study used associative statistical analysis and data analysis using Partial Least Square (SEM-PLS). Data processing in this study uses the Smart PLS 3 Software program. The results of this study indicate that Price has a positive and significant influence on Purchasing Decisions, Price has a positive and significant influence on Perceived Value, Product Quality has a positive and significant influence on Purchase Decisions, Product Quality has a positive and significant influence on Perceived Value, Hedonism Lifestyle has a positive and significant influence on Purchasing Decisions, Hedonism Lifestyle has a positive and significant influence on Perceived Value, Perceived Value has a positive and significant influence on Purchase Decisions, Price has a positive and insignificant influence significant effect on Purchasing Decisions mediated by Perceived Value, Product Quality has a positive and significant influence on Purchase Decisions mediated by Perceived Value, Hedonism Lifestyle has a positive and significant effect t on Purchasing Decisions mediated by Perceived Value.